Iqbal: the Renaissance Man from the Muslim world - Abdul Razak, Mohd Abbas; Machouche, Salah (AHAS KIRKHS, IIUM, 2023)
Allama Muhammad Iqbal (1877-1938) was an eminent Muslim scholar of the early 20th century. As a versatile scholar and leader, he had a mastery over many disciplines of knowledge, like philosophy, poetry, history, civilization, politics, education, law, and mysticism. The unfolding of events during his time challenged him to come up with a new philosophy for the survival of the Muslim Ummah. All his ideas shared through his poetry and philosophy are anchored in the two primary sources of Islam; the Qur’an and the Sunnah of the Holy Prophet (SAW). Poetry and philosophy are the two vehicles he used to get across his ideas to the academics and laity. For the vast majority of the people in the Indian subcontinent, Iqbal was well-known for his invigorating mystical poems. During Iqbal’s time, it was customary for people to spend their leisure time reading and listening to poetry in the media. Though Iqbal’s ideas came under criticism from a small circle of Sufis of his time, during modern times up until now, generally his ideas are well-received by Muslims of all sects and denominations. A little-known fact to many is that, Iqbal is one of the most researched Muslim personalities after the Prophet of Islam SAW. The claim made by some scholars that Iqbal’s ideas are no longer relevant in the modern world is not true. In analyzing the problems in the Muslim world, the researchers have found out that though all Muslim countries are liberated from the clutches of Western colonization, they have not moved very far from the problems highlighted by Iqbal. As a visionary leader and a scholar, Iqbal vehemently opposed the self-denial philosophy, superstitious beliefs, fatalistic way of thinking, slave-mentality, blind imitation of the West, pseudo-mysticism, etc. prevalent among the Muslim community of his time. To remedy the situation, Iqbal developed and introduced his version of the ego philosophy. This new philosophy which he named the ‘Khudi’, calls for the strengthening of the hu-man personality. It was Iqbal’s conviction that with such a philosophy, the Muslim Ummah in the Indian subcontinent and elsewhere in the world would be able to restore the lost dignity, pride and fame of the past (the Golden Age of Islam-750-1258). The word ‘Renaissance’ used in the title should not be mistaken for its use in the European context. Renaissance which means a ‘rebirth’ called for the revival of the Classical learning and wisdom of the Greek and Roman civilizations as opposed to the dominance of the Catholic Church. The Eu-ropean Renaissance was also seen as a revolt and protest against the tyrannical rule of the clergy in Christendom. In the context of Iqbal, he was seen as a ‘reformer’ who called for the practice of the true spirit and dynamism found in the Qur’an and Sunnah against all self-denial philosophy and pseudo-mysticism. In this humble work, the researchers have dwelt upon Iq-bal’s life and work, the condition of the Muslim Ummah of his time, his Khudi philosophy, the hidden potentials of the human ego, how the ego should interact with God, nature and the collective ego of the society, elements that can strengthen and weaken the ego, the ideal society for the growth of the ego, etc. Finally, the researchers would like to state that the publi-cation of this book is an ambitious effort to promote among students of IIUM and elsewhere in the Muslim world, Iqbal’s philosophy and ideas on how to reclaim the lost glory and fame of the Muslim Ummah. The researchers sincerely welcome comments and constructive criticisms from the readers.